Maging akin muli - Diaz-Abaya, Marilou (Quezon City Jesuit Communications Foundation, 2006)
There he meets Fr. Salvador Bautista (Noel Trinidad), 65, fluent in Latin and Italian, a product of the 'Old school'. Ordained just as the reforms of the Second Vatican Council were launched, Fr. Doy had served in several parishes before being assigned to the rural Parish of Santiago Apostol the past five years.
VCD
Marvin Agustin, Nael Trinidad, Sandy Andolong
Keywords: Priesthood; Priests--Philippines.; Feature films